2022
DOI: 10.1111/1752-1688.13043
|View full text |Cite
|
Sign up to set email alerts
|

Early Influence of the COVID‐19 Pandemic on Volunteer Water Monitoring Programs in the United States and Canada

Abstract: Volunteer water monitoring programs generate new scientific knowledge, contribute data to decision‐making processes, and increase social networks, technical knowledge, and skills of participants. Declaration of the COVID‐19 pandemic threatened the ability of these programs to continue to engage volunteers to achieve such outcomes. A national water monitoring network hosted a brainstorming webinar to facilitate communication across programs to identify potential solutions to pandemic‐influenced challenges. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For instance, enhanced gaming functions (e.g., leader boards), publicly displayed volunteer recognition accolades (e.g., years of participation lists), or other types of online acknowledgement (Cappa et al, 2018) could be established. Another option might be to establish online gatherings for volunteers, which was observed to be an effective way to bring together participants from expansive geographic areas during the COVID-19 pandemic (Stepenuck and Carr, 2022). The CrowdWater project now organizes online meet-the-team events, where participants can also meet each other.…”
Section: Networking Enjoyment and Funmentioning
confidence: 99%
“…For instance, enhanced gaming functions (e.g., leader boards), publicly displayed volunteer recognition accolades (e.g., years of participation lists), or other types of online acknowledgement (Cappa et al, 2018) could be established. Another option might be to establish online gatherings for volunteers, which was observed to be an effective way to bring together participants from expansive geographic areas during the COVID-19 pandemic (Stepenuck and Carr, 2022). The CrowdWater project now organizes online meet-the-team events, where participants can also meet each other.…”
Section: Networking Enjoyment and Funmentioning
confidence: 99%
“…Although these programs can be useful for biodiversity monitoring, water monitoring, which often requires access to a laboratory, was harder to conduct during the pandemic; the largest community science program in Ontario, the Lake Partner Program, was shut down for the entirety of the spring and summer of 2020 (Dorset Environmental Science Centre 2020). Alternatively, a survey of U.S. and Canadian community science water monitoring program coordinators (Stepenuck and Carr 2022) found that 72% of programs planned to continue through the 2020 field season, despite delays. highlighting the flexibility of community science as a water monitoring tool.…”
Section: Introductionmentioning
confidence: 99%